EU Renewable Energy Governance and the Ukraine War: Moving Ahead Through Strategic Flexibility? - Buzogány, Aron (2023)
When faced with highly heterogeneous national conditions and preferences, the EU has often resorted to differentiation to ensure political support for advancing common policies. Despite growing scholarly interest in differentiation in the EU, conceptual clarity and empirical evidence of different forms of differentiation are still in a nascent stage. Particularly the use of differentiation in times of crisis needs to be better understood. To address this research gap, we investigate differentiation in the EU renewable energy policy in response to the crisis stirred by Russia’s full-scale invasion of Ukraine. We find that the EU successfully used the Ukraine crisis to increase the ambition of renewable energy policy, but this was accompanied by various and often novel forms of differentiation. Rather than formally exempting countries from common EU provisions (differentiated integration), EU decision-makers strategically incorporated flexibility in implementation, often tailored to a few outlier countries. Strategic flexibility was instrumental in overcoming political disagreements among national governments and adopting a more ambitious and comprehensive renewable energy policy. Our findings contribute conceptually and empirically to understanding various forms of differentiation in EU policymaking and how they are employed to facilitate the building of political majorities during crises.